Analysis of Attachment Styles and Relationship Dynamics in Early Adulthood: Implications for the Need for Premarital Counseling - Alfalathi, Siti Aminah; Mayra, Zara; Suryaman, Neng Triyaningsih; Wahjuningtijas, Rindang; Saefudin, Dery (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
Premarital counseling is increasingly recognized as important in Indonesia, yet the influence of attachment styles and relationship conditions on counseling needs among young adults is not well understood. This study examined the distribution of attachment styles, relationship conditions, and demographics, and their effect on the perceived need for premarital counseling. A cross-sectional survey was conducted with 480 young adults aged 18–40 using self-report questionnaires, and rare-event penalized logistic regression accounted for the highly unbalanced outcome. Results showed moderate levels of secure, disorganized, anxious, and avoidant attachment, with secure attachment slightly more common. Almost all participants (99.4%) reported needing premarital counseling. Regression analysis indicated that higher secure attachment scores were positively associated with counseling needs (OR = 1.82). Most participants were single, without children, and reported neutral to positive relationship conditions. These findings suggest young adults recognize the value of premarital counseling for emotional preparation and relational skill development, highlighting the need for interventions tailored to individual attachment profiles. Counseling programs should be culturally sensitive, adaptable, and attachment-informed, emphasizing communication, conflict resolution, and self-reflection to support long-term relationship satisfaction. Future research should adopt longitudinal and mixed-method approaches to better understand motivations and counseling needs.